2009
DOI: 10.1007/s12594-009-0054-4
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of the Bondla layered mafic-ultramafic complex, Usgaon, Goa

Abstract: The Bondla mafic-ultramafic complex is a layered intrusion that consists predominantly of peridotites and gabbronorites. A chromitite-pyroxenite-troctolite horizon serves as a marker to subdivide the intrusion into two zones. The Lower Zone displays gravity stratified layers of chromite that alternate with those of olivine, which up-section are followed by olivine+pyroxene-chromite cumulates. The Upper Zone comprises gabbroic rocks that exhibit uniform layering. On the basis of modal and cryptic variation exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Metamorphic garnets overgrowing the tectonic fabric in granitoids are common in the well‐foliated/gneissose varieties in the south but are absent in the weakly foliated granitoids northwards within the corridor. The lithologies in the corridor are in sharp contrast to those in the Goa Schist Belt (WDC) dominated by NNW‐trending bands of greenschist facies metagreywacke (chlorite‐muscovite ± calcite ± biotite schist), Banded Iron Formation, amphibolite (actinolite‐chlorite schist), polymict and quartz conglomerate and quartzite, and mafic‐ultramafic complexes comprising gabbro, troctolite, wehrlite, dunite, peridotite, pyroxenite, and chromitite, and chromite‐bearing serpentinite [ Jena , , ; Geological Survey of India , ; Dessai et al ., ; Ishwar‐Kumar et al ., ; Rekha et al ., ]. The Quepem granitoid pluton intrusive into the schists is deformed along with the supracrustals [ Rekha et al ., ].…”
Section: Geological Settingmentioning
confidence: 99%
“…Metamorphic garnets overgrowing the tectonic fabric in granitoids are common in the well‐foliated/gneissose varieties in the south but are absent in the weakly foliated granitoids northwards within the corridor. The lithologies in the corridor are in sharp contrast to those in the Goa Schist Belt (WDC) dominated by NNW‐trending bands of greenschist facies metagreywacke (chlorite‐muscovite ± calcite ± biotite schist), Banded Iron Formation, amphibolite (actinolite‐chlorite schist), polymict and quartz conglomerate and quartzite, and mafic‐ultramafic complexes comprising gabbro, troctolite, wehrlite, dunite, peridotite, pyroxenite, and chromitite, and chromite‐bearing serpentinite [ Jena , , ; Geological Survey of India , ; Dessai et al ., ; Ishwar‐Kumar et al ., ; Rekha et al ., ]. The Quepem granitoid pluton intrusive into the schists is deformed along with the supracrustals [ Rekha et al ., ].…”
Section: Geological Settingmentioning
confidence: 99%
“…The Chandranath granite gneiss was considered to be syntectonic with the first phase of folding, the Tamdi felspathic gneiss and the Dudhsagar granite were considered to be synkinematic with the second phase, whereas the Canacona granite was considered to be post-tectonic (Gokul et al 1985). In the light of the recent work (Dhoundial et al 1987;Devaraju et al 2007Devaraju et al , 2010Dessai et al 2009) especially on the granitic gneisses, greenstones and the intrusive granites from representative sections, it is proposed to revisit the classification of the greenstones from this area. The Goa Group of Gokul et al (1985) needs to be integrated (see also Devaraju et al 2010) with the contiguous Dharwar Supergroup of WDC, as otherwise it would give an erroneous impression of forming a separate stratigraphic entity within the Dharwar craton.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Jena, 1980Jena, , 1985 which were later identified to form a layered peridotites-gabbro complex (e.g. Balakrishnan et al 1992;Dessai et al 2009). Dessai and Peshwa (1982) have shown that the complex is intruded along a major shear zone that runs NW-SE.…”
Section: Layered Intrusionmentioning
confidence: 99%
See 2 more Smart Citations